The State azerbaydzhanskoe: demokratycheskaya, pravovaya, svetskaya, unytarnaya republic - Кулієв, Ібрагім Орудж огли; Муршудова, Саміра Хошбахт гизи (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article is devoted bases of a state system of the Azerbaijan Republic. The Constitution of the Azerbaijan Republic defines intentions for realization. They act in the form of accurately formulated purposes to which the people aspire.